2005
DOI: 10.1148/radiol.2352040583
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Patients with Blunt Abdominal Trauma: Performance of Screening US

Abstract: In patients who are hypotensive after blunt abdominal trauma and not hemodynamically stable enough to undergo diagnostic CT, negative US findings virtually exclude surgical injury, while positive US findings indicate surgical injury in 64% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 30 publications
3
42
0
2
Order By: Relevance
“…This facility was not available at the facilities during the period of study. We had to rely on ultrasonography (which is operator dependent) and clinical judgment to determine those patients that would require emergent surgical intervention 28 . Retrospectively we have found that sound clinical judgment with at least an abdomino-pelvic ultrasonography (in suspected gut perforation or abdominal trauma) and/or plain abdominal x-ray (in suspected intestinal obstruction) gave a diagnostic accuracy of 90.4% and negative laparotomy rate was zero percent.…”
Section: Discussionmentioning
confidence: 99%
“…This facility was not available at the facilities during the period of study. We had to rely on ultrasonography (which is operator dependent) and clinical judgment to determine those patients that would require emergent surgical intervention 28 . Retrospectively we have found that sound clinical judgment with at least an abdomino-pelvic ultrasonography (in suspected gut perforation or abdominal trauma) and/or plain abdominal x-ray (in suspected intestinal obstruction) gave a diagnostic accuracy of 90.4% and negative laparotomy rate was zero percent.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal injuries are the third common cause of traumatic death after head and chest injuries [11]. Diagnostic peritoneal lavage (DPL) has been done Patients, Correlation with Computed Tomography historically to detect hemoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the FAST scan is particularly beneficial in the hypotensive trauma patient whose source of hypotension is unclear. 17 Despite the encouraging literature, it is important to remember that all ultrasound, including the FAST exam, is dependent on the training and experience of the clinician. A study evaluating non-radiologist physicians (surgeons and emergency medicine physicians) found that while the initial error rate for FAST scans was 17%, it fell to 5% after performing ten exams.…”
Section: Ultrasound In Blunt Trauma Abdomenmentioning
confidence: 99%